PENGEMBANGAN MEDIA FLIPBOOK BERBASIS KEARIFAN LOKAL KOTA SEMARANG MENGENAI PENGALAMANKU DI TEMPAT WISATA SEBAGAI LITERASI SISWA KELAS II SEKOLAH DASAR - Tania Ike Nur Rahmawati; Mira Azizah; Fine Reffiane (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning in schools has an important role in conveying knowledge to students. Submission of this material can be obtained from the environment around where students live which is packaged in a story as student literacy. This study aims to produce flipbook media based on local wisdom in Semarang City regarding My Experience in Tourist Attractions as literacy for second grade elementary school students who meet valid and practical criteria. This research is a type of Research and Development (R&D) research with the ADDIE model which includes five stages, namely: analyze, design, development, implementation, evaluation. The subjects in this study were media expert validators, material experts, and the responses of class II students at SDN Gajahmungkur 04 with a total of 16 students. The research instruments included validation questionnaire sheets (media and materials) and practicality questionnaire sheets. The results showed that flipbook media based on local wisdom in Semarang City regarding My Experience in Tourist Attractions as literacy for second grade elementary school students obtained a validation percentage by media experts of 95.59% with very valid criteria, the percentage of validation by material experts was 100% with very valid criteria. valid. The average percentage of validation is 97.79% with very valid criteria. The percentage of the practicality test from the results of the student questionnaire obtained 90.6% with very practical criteria. Based on the results of the study, it can be concluded that this study produced flipbook media based on local wisdom in the City of Semarang regarding My Experience in Tourist Attractions as Literacy for Class II Elementary School Students which is valid and practical.